2006
DOI: 10.2737/fpl-rp-634
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of silvicultural treatments and biomass use for reducing fire hazard in western states

Abstract: The use of trade or firm names in this publication is for reader information and does not imply endorsement by the United States Department of Agriculture (USDA) of any product or service. The USDA prohibits discrimination in all its programs and activities on the basis of race, color, national origin, age, disability, and where applicable, sex, marital status, familial status, parental status, religion, sexual orientation, genetic information, political beliefs, reprisal, or because all or a part of an indivi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 16 publications
1
36
0
Order By: Relevance
“…[These operations are visualized in Figures 3.1 and 3.2.] A Web-based tool, the Fuel Treatment Evaluator, was subsequently developed to identify, evaluate, and prioritize fuel treatment opportunities that would remove excess biomass and promote a more natural fire regime pattern, with recurrence of less severe fire Skog et al, 2006 limitations, and merchandizing thinnings into two utilization groups (conventional forest products and bioenergy products).…”
Section: Text Box 32 | Forest Resources Of the United Statesmentioning
confidence: 99%
“…[These operations are visualized in Figures 3.1 and 3.2.] A Web-based tool, the Fuel Treatment Evaluator, was subsequently developed to identify, evaluate, and prioritize fuel treatment opportunities that would remove excess biomass and promote a more natural fire regime pattern, with recurrence of less severe fire Skog et al, 2006 limitations, and merchandizing thinnings into two utilization groups (conventional forest products and bioenergy products).…”
Section: Text Box 32 | Forest Resources Of the United Statesmentioning
confidence: 99%
“…Thus, in addition to modeling wood supply by size class of trees and logs, we used harvest cost models to obtain estimates for FTM-West of harvesting costs unique to each tree size class. Harvesting costs for wood removed in fuel treatments were estimated by the FTE 3.0 program (Skog et al, 2006), using the calculation routine from "My Fuel Treatment Planner" (Biesecker and Fight, 2006). Timber harvesting costs for conventional timber supply were estimated by tree diameter class using a conventional timber harvest cost model by Keegan et al (2002).…”
Section: Special Considerations In Designing Ftm-westmentioning
confidence: 99%
“…Estimates of potential wood supply from hypothetical fuel treatment programs and corresponding harvest costs for FTMWest were developed using the Fuel Treatment Evaluator 3.0 (Skog et al, 2006). FTE 3.0 is a web-based tool that selects forest areas for treatment and applies simulated treatments based on extensive forest inventory sample plot data on timberland in twelve western U.S. states.…”
Section: Estimation Of Wood Supply From Thinning Programs and Associamentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Skog et al (2006) found that slope can play a key role influencing net financial returns on fuel reduction treatments. Fiedler et al (1999) evaluated restoration thinnings for ponderosa pine forests and found that on slopes of less than 35 percent, net revenues of $950 per acre were possible when a roundwoodpulpwood market was present.…”
Section: Biomass Harvesting and Fire Hazard Reductionmentioning
confidence: 99%